CREATIVE DEVELOPMENT OF THE YOUTH IS THE WAY OF INCREASE OF THE CREATIVE MANAGEMENT (Scientific journal of the Fergana State University, 2023)
This article discusses issues related with the life of young people, their ability of creative approach, the development of creativity. The author characterizes the creative approach to the study of the situation, thus, revealing that the creativity is creation, the ability to form, create something new, using extraordinary schemes, departing from traditional thinking.  With the help of creative thinking, we can generate new ideas, act differently, and find ways out of difficult situations. The development of youth creativity should serve to uplift the creative management of the society.